Double chain system for online and offline medical data sharing viaprivate and consortium blockchain: A system design study - Li, Chaoran; Liu, Jusheng; Qian, Guanyu; Wang, Ziyi; Han, Jingti (Frontiers in Public Health, 2022)
With the informatization development and digital construction in the healthcare industry, electronic medical records and Internet medicine facilitate people’s medical treatment. However, the current data storage method has the risk of data loss, leakage, and tampering, and can’t support extensive and secure sharing of medical data. To realize effective and secure medical data storage and sharing among offline medical institutions and Internet medicine platforms, this study used a combined private blockchain and consortium blockchain to design a medical blockchain double-chain system (MBDS). This system can store encrypted medical data in distributed storage mode and systematically integrate the medical data of patients in offline medical institutions and Internet medicine platforms, to achieve equality, credibility, and data sharing among participating nodes. The MBDS system constructed in this study incorporated Internet medicine care services into the current healthcare system and provided new solutions and practical guidance for the future development of collaborative medical care. This study helped to solve the problems of medical data interconnection and resource sharing, improve the efficiency and effect of disease diagnosis, alleviate the contradiction between doctors and patients, and facilitate personal health management. This study has substantial theoretical and practical implications for the research and application of medical data storage and sharing.